Venous catheter sepsis - Nin Ferrari, José; Amonte, Pedro; Correa, Humberto (Cirugía del Uruguay, 1979)
Retrospectic review of case histories of patients interned in an Intensive Care Unit disclosed that 13 % (7,7 % of all septic cases) had been caused by endo·venous invasive procedures. This group of patients shared the clinical characteristics of septic patients in general and mortality was 64 %- Pathogenic agent was pathogenic Staphylococcus aureus, 61 %; E. Coli, 30 %; and monilias, 8 % . Attention is drawn to the risk of contamination of venous pathway, in particular that used in control and replacement of CVP; measures for the preventing and treatment of sepsis caused by venous catheter are also listed.